A Proposed Software Development Methodology for the Hospital Management Information Systems - Rajulben Shah, Dr. Papri Das; Dr. Anurag Dixit (Journal of Informatics Education and Research, 2025)
Information System design and development needs to consider systematic and disciplined software development methodology in today’s revolutionary world. Each of the system development methodologies has its own characteristics, specific interest, coverage etc. Digitalization in the hospital management information systems and processes is essential in the era of globalization and modernization. The hospital management Information system is widely expected to increase patient safety and reduce medical errors. Designing and developing software project needs careful and appropriate software development methodology which helps the developers as a guiding tool to design and develop new systems. In this paper a software development methodology for the hospital management information system has been proposed. It is helpful to solve the challenges of the designing and development of healthcare applications in the modern world of Artificial Intelligence.